P439 Effectiveness and safety of the sequential use of a second and third anti-TNF agent in patients with inflammatory bowel disease: results from the ENEIDA registry. (25th January 2019) - Casanova, M J; Chaparro, M; Mínguez, M; Ricart, E; Taxonera, C; García-López, S; Guardiola, J; López-San Román, A; Iglesias, E; Beltrán, B; Sicilia, B; Vera, M I; et al.
Abstract: Background: The aim of the present study was to investigate the efficacy and safety of the sequential use of a second and a third anti-TNF agent after failing or developing intolerance to an anti-TNF drug. Methods: Patients diagnosed with Crohn's disease (CD) or ulcerative colitis (UC) from ENEIDA registry (a prospectively maintained registry from GETECCU) who switched to another anti-TNF drug after failure or intolerance to a previous anti-TNF, were included. Efficacy, loss of response, and safety of the second and third anti-TNF were evaluated by logistic regression, Kaplan–Meier and Cox regression analyses. Results: In total, 1122 patients that switched to a second anti-TNF were included (50% men, mean age at diagnosis 31 years, 73% CD). The reasons for withdrawal the first anti-TNF were: primary failure (22%), secondary failure (51%), and intolerance (27%). Remission was achieved with the second anti-TNF drug in 45% of patients in the short-term. The rate of remission was similar between CD and UC patients (46% vs. 41%, p = 0.06). There was no difference in remission rates according to the sequence of the anti-TNF administration: infliximab–adalimumab or adalimumab–infliximab (42% vs. 48%, p = 0.07). The factors associated with a lower probability of achieving remission after a second anti-TNF were: combo therapy (OR = 0.5 95% CI = 0.4–0.8), to withdraw the first anti-TNF due to a primary failure (vs. intolerance; OR = 0.6, 95% CI = 0.4–0.9), and to withdraw the first anti-TNF due to secondary failure (vs. intolerance) (OR 0.6, 95% CI = 0.5–0.9). The cumulative incidence of loss of response after achieving remission with the second anti-TNF (median follow-up of 19 months) was 45%: 23% at 1 year and 62% at 5 years. The incidence of loss of response to the second anti-TNF was 19% per patient-year of follow-up. The factors associated with a higher risk of loss of response were: UC vs. CD (HR = 1.6; 95% CI = 1.1–2.1, p = 0.005) and combo therapy (HR = 2.4; 95% CI = 1.8–3, p < 0.0001). Adverse events occurred in 15% of the patients who switched to a second anti-TNF (10% stopped the treatment). Seventy-one patients switched to a third anti-TNF and 55% achieved remission. The incidence of loss of response to a third anti-TNF was 22% per patient-year (median follow-up of 9 months). Seven patients (11%) had adverse events, but only one discontinued the therapy. Conclusions: Almost half of the patients who switched to a second anti-TNF achieved remission; however, a high proportion of them subsequently lost response. Factors associated with loss of response were type of inflammatory bowel disease and combo therapy. Approximately 50% of patients who received a third anti-TNF achieved remission; however, again, a high proportion of them lost response subsequently.